Implementasi pemberian reward pada pembelajaran matematika di kelas V MIN 2 Kota Palembang - Toyba Tulilah; Fuaddilah Ali Sofyan; Nurlaeli Nurlaeli (AL-ASASIYYA: Journal Of Basic Education, 2020)
Reward is basically a response given by the teacher to the behavior or deeds of students who are considered positive, and cause recurrence or increase the behavior. The results of the study show that the teacher has applied a reward (1) Implementation of a reward in Mathematics learning in VA class that has implemented a reward using words of praise, " good "," good "," enthusiasm "and applause. Using prizes in the form of stationery, which are given to students who are able to answer questions. There is also a form of respect that is a good grade will be announced in the school field and awards in the form of certificates, trophies and pocket money given to students who get 1-3 rank from each class (2) The inhibiting factors are financial and time constraints. (3) And the supporting factor is the existence of support from the school in the form of motivational encouragement in the form of a charter given by the school to teachers who are disciplined and have good performance and aim to encourage the enthusiasm of students to compete in learning.